Professional reasoning in the interior design language (Journal of the College of Basic Education, 2019)
The importance of research by contributing to the preparation of a professional language for interior design through the expansion of the dialogue to more than the level of intellectual As for the problem of research has been determined by the absence of a study dealing with this trend in the inference analysis of the language of internal spaces, while the aim of the research is to reach the level of the use of professional reasoning In the design language of the interior spaces, the most important results of the study were the following: - Professional reasoning is the efficient use of Reasoning and three types (deductive and inductive and representative) and as needed if it is at the stage of the formation of a new space language or the stage of reading an existing space- The use of types of Reasoning in different sequences by the designer serves to create different formative dialogues in addition to the manufacture of new ideas.